Public Relations Politik Partai Keadilan Sejahtera dalam Pemilukada Jawa Barat - Khoiruddin Muchtar; Aliyudin Aliyudin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2019)
The research aims to obtain an overview of the media relations of the Prosperous Justice Party in building party image, determining strategies in maintaining positive relations with the media, and utilizing social media in forming the opinions of candidates for governor of West Java in 2018. Research uses constructivist paradigms, qualitative approaches and case study methods . The results of the study show that, political public relations within the Prosperous Justice Party are carried out by building togetherness and consolidation as well as cadre formation in a family and equality manner. Communication within the Prosperous Justice Party began to be addressed and conditioned, especially the spread of information within the PKS. PKS external communication is carried out by building a positive image of the party, building coalitions with other parties, and socializing the characteristics of West Java governor candidates so that they can be accepted by the community. The imaging strategy carried out by the Prosperous Justice Party in the media is done by building good relationships with the media and utilizing social media appropriately as well as utilizing E-mail, blogs, social media or Twitter. PKS vote acquisition as runner-up in 2018 West Java Pilgub shows, the existence of PKS as a party that is quite trusted and calculated.Penelitian bertujuan untuk memperoleh gambaran tentang media relations Partai Keadilan Sejahtera dalam membangun citra partai, menentukan strategi dalam memelihara hubungan positif dengan media, serta pemanfaatan media sosial dalam membentuk opini calon gubernur Jawa Barat Tahun 2018. Penelitian menggunakan paradigm konstruktivis, pendekatan kualitatif dan metode studi kasus. Hasil penelitian menunjukan bahwa, Public relation politik di internal Partai Keadilan Sejahtera dilakukan dengan membangun kebersamaan dan konsolidasi sekaligus dengan pembinaan kader secara kekeluargaan dan kesetaraan. Komunikasi internal PKS mulai dibenahi dan dikondisikan, terutama dalam penyebaaran informasi di internal PKS. Komunikasi eksternal PKS dilakukan dengan membangun citra positip partai, membangun koalisi dengan partai lain, dan mensosialisasikan karakteristik calon gubernur Jawa Barat sehingga bisa diterima oleh masyarakat. Strategi pencitraan yang dilakukan oleh Partai Keadilan Sejahtera di media dilakukan dengan cara membangun hubungan yang baik dengan media dan memanfaatkan media social secara tepat seperti halnya pemanfaatan E-mail, blog, media sosial ataupun Twitter. Perolehan suara PKS sebagai runner up Pilgub Jabar 2018 menunjukan, eksistensi PKS sebagai partai yang cukup dipercaya dan diperhitungkan.